Stable-isotope dilution LC-MS/MS method for quantitative determination of microcystin conjugates with cysteine and glutathione in biotic matrices - Kohoutek, Jiří; Procházková, Tereza; Adamovský, Ondřej; Palíková, Miroslava; Hilscherová, Klára (Analytical and bioanalytical chemistry, 2019)
Microcystins are cyclic peptide toxins with hepatotoxic and tumor-promoting properties, which are produced in significant quantities (up to tens of μg/L) in freshwater cyanobacterial water blooms. Several studies reported microcystin accumulation in fish with possible food transfer to humans. These compounds are further metabolized to cysteine and glutathione conjugates which can be present in tissues in significant concentrations. In this study, we focused on the development and evaluation of robust and highly sensitive SPE-LC-MS/MS method for the analysis of microcystin conjugates in fish tissue samples. For the first time, we demonstrate the use of isotopically labeled internal standards which are essential for accurate and precise determination of analytes in complex biotic matrices. LLOQs of respective microcystin conjugates (signal-to-noise ratio; S/N > 10, peak-to-peak method) ranged from 3.3 to 5.0 ng/g of tissue fresh weight (FW). The calibration was linear within a range of concentrations from 1 to 70 ng/mL for all analyzed conjugates. The precision and repeatability of the method were very good with recoveries in the range of 88.5-107.6% and relative standard deviations between 8.8 and 13.2% for all analytes. In the follow-up study, fully validated method was used for the determination of microcystin conjugate levels in common carp exposed to microcystin-containing cyanobacterial biomass under controlled conditions. Significant amounts of microcystin conjugates (up to 55 ng/g) were found in the tissues of fish after 7 weeks of exposure. Our method was shown to be robust, sensitive, selective, and suitable for the determination of trace levels of microcystin conjugates in fish tissues.
Keywords: Limit of Detection; radioisotopová diluční technika; Cyanobacteria; Reproducibility of Results; biomasa; Glutathione; Cysteine; L-Cysteine; LC-MS/MS; cystein; Tandem Mass Spectrometry; reprodukovatelnost výsledků; glutathion; Radioisotope Dilution Technique; chromatografie kapalinová; Microcystins; sinice; limita detekce; tandemová hmotnostní spektrometrie; Biomass; Chromatography, Liquid; Microcystin; L-Glutathione; mikrocystiny